A Research on the Application of Dynamic Case Method in the Course of International Politics - Wang, Baisong (International Journal For Research In Educational Studies, 2020)
International Politics is a theoretical and practical course. The use of case method, especially dynamic case method, can not only guide students to fully understand and grasp the basic theories of international politics, and make them have scientific and rational analysis and judgment about some real international problems, but also learn and analyze the intricate international political problems and lay a solid foundation to form the correct values.